High-performance sealing rubber material and preparation method thereof
By using in-situ blending technology of fluorosilicone rubber and white carbon black, the shortcomings of existing rubber materials in mechanical and oil resistance are solved, and high-performance sealing rubber materials with excellent mechanical and oil resistance are prepared, suitable for aviation sealing field.
Patent Information
- Application Number
- CN202411310872.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
The existing rubber materials have low mechanical properties and oil resistance, especially in low temperature environments, which are difficult to meet the needs of aviation sealing.
Using fluorosilicone rubber as the matrix, through in-situ blending method and white carbon black as filler, combined with suitable processing technology, a high-performance sealing rubber material that is resistant to wear and oil is prepared to achieve uniform dispersion of reinforcement filler in the rubber matrix. Build a three-dimensional network structure to improve mechanical properties and oil resistance.
The prepared high-performance sealing rubber material exhibits excellent mechanical properties and oil resistance at low temperatures, with tensile strength of 10~11 MPa, elongation of breaking from 200~900%, and brittle temperature of -60 ℃ at low temperature The compressive stress relaxation coefficient maintained in 15# aviation oil for 72 hours is 0.7, which is suitable for aviation sealing fields.
Smart Images

Figure CN119192855A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber materials, and in particular relates to a high-performance sealing rubber material and a preparation method thereof. Background Art
[0002] Rubber is an important part of the chemical industry. Rubber products such as tires, hoses, tapes, rubber rollers, rubber seals, and rubber tape products are widely used in various industries of the national economy, such as automobile production, aircraft manufacturing, crude oil transportation, electronic communications, and hospitals, and have become one of the important basic industries. At present, the basic raw materials of the rubber industry are natural rubber and synthetic rubber. Whether it is natural rubber obtained from nature or synthetic rubber obtained by humans through industrial means, although they have valuable high elasticity and a series of other excellent properties, they still have many shortcomings in performance. For example, the mechanical properties and oil resistance of existing rubber materials are relatively low.
[0003] A Chinese patent with publication number CN104086980A and publication date 2014.10.08 discloses an oil-resistant, low-temperature-resistant and weather-resistant rubber sealing material and its preparation method and application. The rubber sealing material is prepared from the following raw materials by mass: 70-95 parts of mixed polyurethane, 5-30 parts of nitrile rubber or chloroether rubber, 20-80 parts of carbon black, 1-25 parts of ether lipid plasticizer, 1-10 parts of acid absorber, 1-5 parts of anti-adhesive agent, 0.5-5 parts of ketone amine antioxidant, 0.5-5 parts of diphenylamine antioxidant, 0.5-5 parts of imidazole antioxidant, 0.5-5 parts of peroxide, and 0.5-5 parts of cross-linking agent. The rubber has the following disadvantages: nitrile rubber is a copolymer of butadiene and acrylonitrile, and the content of acrylonitrile has a greater influence on the various properties of nitrile rubber. Generally, the higher the acrylonitrile content, the better the processing performance and tensile strength of the nitrile rubber. However, the high nitrile content reduces its low temperature resistance. Generally speaking, the Tg of nitrile rubber is usually between -45 and -25°C. In this patent, the Tg range of the prepared nitrile rubber is between -45 and -35°C. Compared with this technology, the fluorosilicone rubber prepared by in-situ blending using fluorosilicone rubber as the matrix has a lower Tg (-60 to -50°C), better low temperature resistance, and can better meet the needs of practical applications. Summary of the invention
[0004] In order to solve the problems of the prior art, a high-performance sealing rubber material and a preparation method are proposed. Fluorosilicone rubber is used as a matrix, and white carbon black is used as a filler. The reinforcing filler is evenly dispersed in the rubber matrix by an in-situ blending method, and a wear-resistant and oil-resistant rubber sealing material is prepared. The material prepared by the present invention has a simple processing technology and is easy to industrialize, and the material has excellent mechanical properties.
[0005] The objective of the present invention is achieved through the following technical solutions: A high-performance sealing rubber material comprises the following components in parts by weight: 100 parts of fluorosilicone rubber, 0.1 to 0.8 parts of a vulcanizing agent, 10 to 35 parts of a reinforcing filler, 1 to 2 parts of a heat-resistant agent, and 0.5 to 2 parts of a black dye.
[0006] Preferably, the molecular weight of the fluorosilicone rubber is ≥8*10 5 .
[0007] Preferably, the vulcanizing agent is a mixture of one or more of liquid dipentane, solid dipentane, dicumyl peroxide, benzamide peroxide, di-tert-butyl peroxide, and tert-butyl perbenzoate.
[0008] Preferably, the reinforcing filler is a mixture of one or more of fumed silica and precipitated silica.
[0009] Preferably, the heat-resistant agent is a mixture of one or more of titanium dioxide, tin dioxide, iron oxide, copper oxide, nickel oxide, cobalt oxide, and chromium oxide.
[0010] Preferably, the black dye is carbon black.
[0011] A preparation method of a high-performance sealing rubber material comprises the following steps: adding 100 parts of fluorosilicone rubber to a kneader, evacuating the kneader to a vacuum state and continuously stirring, heating to 140°C and maintaining the temperature for 4 hours, and then cooling to room temperature; adding a reinforcing filler to the kneader, and continuously stirring in the kneader for 1 hour to obtain an in-situ blended fluorosilicone rubber; adding the in-situ blended fluorosilicone rubber to an internal mixer for stirring, and kneading at room temperature for 5 minutes, with a rotation speed set to 50 rpm; adding a heat-resistant agent to the internal mixer for mixing and stirring, and kneading at room temperature for 5 minutes, with a rotation speed set to 50 rpm; adding a dye to the internal mixer for continuous mixing and stirring, and kneading at room temperature for 5 minutes, with a rotation speed set to 50 rpm; adding a vulcanizing agent to the internal mixer for mixing and stirring, and kneading at room temperature for 10 minutes, with a rotation speed set to 50 rpm to obtain the kneaded fluorosilicone rubber; passing the kneaded fluorosilicone rubber through a double-roll open mill to obtain a desired mixed rubber, and the mixed rubber can be subjected to hot pressing and two-stage vulcanization to obtain a high-performance sealing rubber material.
[0012] Preferably, the rubber mix is thin-passed in a double-roll mill 8 to 12 times.
[0013] Preferably, the hot pressing temperature of the rubber mix is 160-170° C., the pressure is 10-20 MPa, and the time is 10-20 min.
[0014] Preferably, the second-stage vulcanization temperature of the vulcanized rubber is 200-250° C., and the second-stage vulcanization time is 2-4 h.
[0015] The beneficial effects of this technical solution are as follows: 1. The present invention provides a high-performance sealing rubber material, which takes fluorosilicone rubber as a matrix, uses white carbon black as a filler, and achieves uniform dispersion of the reinforcing filler in the rubber matrix by adopting a suitable processing technology and an in-situ blending method, thereby preparing a wear-resistant and oil-resistant rubber sealing material.
[0016] 2. The present invention provides a method for preparing a high-performance sealing rubber material, which realizes uniform dispersion of reinforcing fillers in fluorosilicone rubber by mechanical blending, and constructs a three-dimensional network structure between reinforcing fillers and rubber matrix through hydrogen bonds and van der Waals action, achieving excellent reinforcement effect. The mechanical properties of the rubber material were tested according to the test method specified in GB / T 528-2009. The tensile strength of the fluorosilicone rubber material was 10-11 MPa, and the elongation at break was 200-900%. The mechanical property test results were better than most silicone rubbers and fluorosilicone rubbers reported. The low-temperature brittle temperature of the rubber material was tested according to the test method specified in GB / T 1682-2014. The low-temperature brittle temperature of the fluorosilicone rubber material can reach -60 ℃. Through the oil resistance test, the compressive stress relaxation coefficient was 0.7 after swelling in 15# aviation oil at a temperature of 70 ℃ for 72 hours. The above results show that the wear-resistant and oil-resistant fluorosilicone rubber sealing material prepared by this method has excellent mechanical properties and oil resistance, and can be used in the field of aviation sealing. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 1 is the stress-strain curve of Example 1, Example 2 and Example 3; Figure 2 is a scanning electron microscope image of Example 3; Figure 3 This is a transmission electron microscope image of Example 3. DETAILED DESCRIPTION
[0018] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0019] The fluorosilicone rubber in Examples 1 to 13 is prepared by the following method: γ-trifluoropropylmethyltrisiloxane and octamethylcyclotetrasiloxane are added to a dry kneader, stirred at 70 ° C for 1 h, and dehydrated. Then tetramethylammonium hydroxide pentahydrate is added to the reactor at a mass ratio of 100:2. The temperature is raised to 70-80 ° C for reaction, and low boiling points are removed. High-purity nitrogen is introduced, the reaction is carried out at 70 ° C for 1 h, the temperature is raised to 104-106 ° C, distilled water is added, the reaction is continued for 2 h with stirring, and then the temperature is raised to 160 ° C and maintained for 1 h, the cyclic small molecule by-products in the product system are removed, and then the fluorosilicone rubber is obtained by terminalization at 160 ° C and a vacuum degree of about -0.1 MPa.
[0020] Example 1 Add 100 parts of fluorosilicone rubber to the kneader, evacuate the kneader and continue stirring, heat up to 140°C, maintain for 4 hours, and then cool to room temperature. Weigh 20 parts of fumed silica according to the formula ratio, continue stirring in the kneader for 1 hour, and obtain fluorosilicone rubber with in-situ blended silica. Add the in-situ blended fluorosilicone rubber to the internal mixer for stirring, and mix at room temperature for 5 minutes, with the speed set to 50 rpm. Add 2 parts by mass of heat-resistant titanium dioxide, stir at 50 rpm for 5 minutes at room temperature, then add 1 part by mass of carbon black dye, continue stirring at 50 rpm for 5 minutes at room temperature, weigh 0.53 parts by mass of liquid dipentadienyl vulcanizer and slowly add it to the fluorosilicone rubber, and stir at 50 rpm for 10 minutes at room temperature. The rubber mix was thinned 10 times in a two-roll open mill, and then hot-pressed in a flat vulcanizer at a temperature of 160°C, a time of 15 min, and a pressure of 10 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 200°C and a time of 4 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0021] Example 2 Add 100 parts of fluorosilicone rubber to the kneader, evacuate the kneader and continue stirring, heat to 140°C, maintain for 4 hours, and then cool to room temperature. Weigh 27 parts of fumed silica according to the formula ratio, continue stirring in the kneader for 1 hour, and obtain fluorosilicone rubber with in-situ blended silica. Add the in-situ blended fluorosilicone rubber to the internal mixer for stirring, and mix at room temperature for 5 minutes, with the speed set to 50 rpm. Add 2 parts by mass of heat-resistant titanium dioxide, stir at 50 rpm for 5 minutes at room temperature, then add 1 part by mass of carbon black dye, continue stirring at 50 rpm for 5 minutes at room temperature, weigh 0.53 parts by mass of liquid dipentadienyl vulcanizer and slowly add it to the fluorosilicone rubber, and stir at 50 rpm for 10 minutes at room temperature. The rubber mix was thinned 10 times in a two-roll open mill, and then hot-pressed in a flat vulcanizer at a temperature of 160°C, a time of 15 min, and a pressure of 10 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 200°C and a time of 4 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0022] Example 3 Add 100 parts of fluorosilicone rubber to the kneader, evacuate the kneader and continue stirring, heat up to 140°C, maintain for 4 hours, and then cool to room temperature. Weigh 31 parts of fumed silica according to the formula ratio, continue stirring in the kneader for 1 hour, and obtain fluorosilicone rubber with in-situ blended silica. Add the in-situ blended fluorosilicone rubber to the internal mixer for stirring, and mix at room temperature for 5 minutes, with the speed set to 50 rpm. Add 2 parts by mass of heat-resistant titanium dioxide, stir at 50 rpm for 5 minutes at room temperature, then add 1 part by mass of carbon black dye, continue stirring at 50 rpm for 5 minutes at room temperature, weigh 0.53 parts by mass of liquid dipentadienyl vulcanizer and slowly add it to the fluorosilicone rubber, and stir at 50 rpm for 10 minutes at room temperature. The rubber mix was thinned 10 times in a two-roll open mill, and then hot-pressed in a flat vulcanizer at a temperature of 160°C, a time of 15 min, and a pressure of 10 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 200°C and a time of 4 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0023] Example 4 Add 100 parts of fluorosilicone rubber to the kneader, evacuate the kneader and continue stirring, heat up to 140°C, maintain for 4 hours, and then cool to room temperature. Weigh 25 parts of fumed silica according to the formula ratio, continue stirring in the kneader for 1 hour, and obtain fluorosilicone rubber with in-situ blended silica. Add the in-situ blended fluorosilicone rubber to the internal mixer for stirring, and mix at room temperature for 5 minutes, with the speed set to 50 rpm. Add 2 parts by mass of heat-resistant titanium dioxide, stir at 50 rpm for 5 minutes at room temperature, then add 1 part by mass of carbon black dye, continue stirring at 50 rpm for 5 minutes at room temperature, weigh 0.3 parts by mass of liquid dipentadienyl vulcanizer and slowly add it to the fluorosilicone rubber, and stir at 50 rpm for 10 minutes at room temperature. The rubber mix was thinned 10 times in a two-roll open mill, and then hot-pressed on a flat vulcanizer at a temperature of 170°C, a time of 10 min, and a pressure of 15 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 200°C and a time of 4 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0024] Example 5 Add 100 parts of fluorosilicone rubber to the kneader, evacuate the kneader and continue stirring, heat to 140°C, maintain for 4 hours, and then cool to room temperature. Weigh 20 parts of fumed silica according to the formula ratio, continue stirring in the kneader for 1 hour to obtain fluorosilicone rubber with in-situ blended silica. Add the in-situ blended fluorosilicone rubber to the internal mixer for stirring, and mix at room temperature for 5 minutes with the speed set to 50 rpm. Add 2 parts by mass of heat-resistant iron oxide, stir at 50 rpm for 5 minutes at room temperature, then add 1 part by mass of carbon black dye, continue stirring at 50 rpm for 5 minutes at room temperature, weigh 0.4 parts by mass of solid dipentadienyl vulcanizer and slowly add it to the fluorosilicone rubber, and stir at 50 rpm for 10 minutes at room temperature. The rubber mix was thinned 10 times in a two-roll open mill, and then hot-pressed in a flat vulcanizer at a temperature of 170°C, a time of 10 min, and a pressure of 15 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 230°C and a time of 3 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0025] Example 6 Add 100 parts of fluorosilicone rubber to the kneader, evacuate the kneader and continue stirring, heat to 140°C, maintain for 4 hours, and then cool to room temperature. Weigh 31 parts of precipitated silica according to the formula ratio, continue stirring in the kneader for 1 hour, and obtain fluorosilicone rubber with in-situ blended silica. Add the in-situ blended fluorosilicone rubber to the internal mixer for stirring, and mix at room temperature for 5 minutes, with the speed set to 50 rpm. Add 2 parts by mass of heat-resistant titanium dioxide, stir at 50 rpm for 5 minutes at room temperature, then add 1 part by mass of carbon black dye, continue stirring at 50 rpm for 5 minutes at room temperature, weigh 0.53 parts by mass of vulcanizing agent diisopropylbenzene peroxide and slowly add it to the fluorosilicone rubber, and stir at 50 rpm for 10 minutes at room temperature. The mixed rubber was thinned 10 times in a two-roll open mill, and the mixed rubber was hot-pressed on a flat vulcanizer at a temperature of 170 °C, a time of 10 min, and a pressure of 15 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 200 °C and a time of 4 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0026] Example 7 Add 100 parts of fluorosilicone rubber to the kneader, evacuate the kneader and continue stirring, heat to 140°C, maintain for 4 hours, and then cool to room temperature. Weigh 20 parts of precipitated silica according to the formula ratio, continue stirring in the kneader for 1 hour, and obtain fluorosilicone rubber with in-situ blended silica. Add the in-situ blended fluorosilicone rubber to the internal mixer for stirring, and mix at room temperature for 5 minutes, with the speed set to 50 rpm. Add 2 parts by mass of heat-resistant agent chromium oxide, stir at 50 rpm for 5 minutes at room temperature, then add 1 part by mass of carbon black dye, continue stirring at 50 rpm for 5 minutes at room temperature, weigh 0.6 parts by mass of vulcanizing agent benzamide peroxide and slowly add it to the fluorosilicone rubber, and stir at 50 rpm for 10 minutes at room temperature. The rubber mix was thinned 10 times in a two-roll open mill, and then hot-pressed on a flat vulcanizer at a temperature of 170 °C, a time of 15 min, and a pressure of 15 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 200 °C and a time of 4 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0027] Example 8 Add 100 parts of fluorosilicone rubber to the kneader, evacuate the kneader and continue stirring, heat to 140°C, maintain for 4 hours, and then cool to room temperature. Weigh 27 parts of precipitated silica according to the formula ratio, continue stirring in the kneader for 1 hour, and obtain fluorosilicone rubber with in-situ blended silica. Add the in-situ blended fluorosilicone rubber to the internal mixer for stirring, and mix at room temperature for 5 minutes, with the speed set to 50 rpm. Add 2 parts by mass of heat-resistant cobalt oxide, stir at 50 rpm for 5 minutes at room temperature, then add 1 part by mass of inorganic dye, continue stirring at 50 rpm for 5 minutes at room temperature, weigh 0.53 parts by mass of vulcanizing agent di-tert-butyl peroxide and slowly add it to the fluorosilicone rubber, and stir at 50 rpm for 10 minutes at room temperature. The rubber mix was thinned 10 times in a two-roll open mill, and then hot-pressed in a flat vulcanizer at a temperature of 170 °C, a time of 10 min, and a pressure of 20 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 200 °C and a time of 4 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0028] Example 9 Add 100 parts of fluorosilicone rubber to the kneader, evacuate the kneader and continue stirring, heat to 140°C, maintain for 4 hours, and then cool to room temperature. Weigh 31 parts of fumed silica according to the formula ratio, continue stirring in the kneader for 1 hour, and obtain fluorosilicone rubber with in-situ blended silica. Add the in-situ blended fluorosilicone rubber to the internal mixer for stirring, and mix at room temperature for 5 minutes, with the speed set to 50 rpm. Add 2 parts by mass of heat-resistant nickel oxide, stir at 50 rpm for 5 minutes at room temperature, then add 1 part by mass of inorganic dye, continue stirring at 50 rpm for 5 minutes at room temperature, weigh 0.8 parts by mass of vulcanizing agent diisopropylbenzene peroxide and slowly add it to the fluorosilicone rubber, and stir at 50 rpm for 10 minutes at room temperature. The rubber mix was thinned 10 times in a two-roll open mill, and then hot-pressed in a flat vulcanizer at a temperature of 170 °C, a time of 10 min, and a pressure of 20 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 200 °C and a time of 4 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0029] Example 10 Add 100 parts of fluorosilicone rubber to the kneader, evacuate the kneader and continue stirring, heat to 140°C, maintain for 4 hours, and then cool to room temperature. Weigh 31 parts of fumed silica according to the formula ratio, continue stirring in the kneader for 1 hour, and obtain fluorosilicone rubber with in-situ blended silica. Add the in-situ blended fluorosilicone rubber to the internal mixer for stirring, and mix at room temperature for 5 minutes, with the speed set to 50 rpm. Add 2 parts by mass of heat-resistant cobalt oxide, stir at 50 rpm for 5 minutes at room temperature, then add 1 part by mass of carbon black dye, continue stirring at 50 rpm for 5 minutes at room temperature, weigh 0.6 parts by mass of vulcanizing agent tert-butyl perbenzoate and slowly add it to the fluorosilicone rubber, and stir at 50 rpm for 10 minutes at room temperature. The rubber mix was thinned 12 times in a two-roll open mill, and then hot-pressed on a flat vulcanizer at a temperature of 160 °C, a time of 15 min, and a pressure of 15 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 200 °C and a time of 4 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0030] Embodiment 11 Add 100 parts of fluorosilicone rubber to the kneader, evacuate the kneader and continue stirring, heat to 140°C, maintain for 4 hours, and then cool to room temperature. Weigh 31 parts of fumed silica according to the formula ratio, continue stirring in the kneader for 1 hour to obtain fluorosilicone rubber with in-situ blended silica. Add the in-situ blended fluorosilicone rubber to the internal mixer for stirring, and mix at room temperature for 5 minutes with the speed set to 50 rpm. Add 2 parts by mass of heat-resistant titanium dioxide, stir at 50 rpm for 5 minutes at room temperature, then add 1 part by mass of carbon black dye, continue stirring at 50 rpm for 5 minutes at room temperature, weigh 0.8 parts by mass of vulcanizing agent benzamide peroxide and slowly add it to the fluorosilicone rubber, and stir at 50 rpm for 10 minutes at room temperature. The mixed rubber was thinned 10 times in a two-roll open mill, and then hot-pressed on a flat vulcanizer at a temperature of 170 °C, a time of 10 min, and a pressure of 20 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 230 °C and a time of 3 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0031] Example 12 Add 100 parts of fluorosilicone rubber to the kneader, evacuate the kneader and continue stirring, heat up to 140°C, maintain for 4 hours, and then cool to room temperature. Weigh 10 parts of fumed silica and precipitated silica according to the formula ratio, continue stirring in the kneader for 1 hour, and obtain fluorosilicone rubber with in-situ blended silica. Add the in-situ blended fluorosilicone rubber to the internal mixer for stirring, and mix at room temperature for 5 minutes, with the speed set to 50 rpm. Add 1 part by mass of heat-resistant agent chromium dioxide and copper oxide, stir at room temperature at 50 rpm for 5 minutes, then add 0.5 parts by mass of carbon black dye, continue stirring at room temperature at 50 rpm for 5 minutes, weigh 0.1 parts by mass of solid dipentadiene and benzamide peroxide of the vulcanizing agent and slowly add them to the fluorosilicone rubber, and stir at room temperature at 50 rpm for 10 minutes. The rubber mix was thinned 8 times in a two-roll open mill, and then hot-pressed in a flat vulcanizer at a temperature of 165°C, a time of 20 min, and a pressure of 20 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 250°C and a time of 2 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0032] Embodiment 13 100 parts of fluorosilicone rubber were added to the kneader, the kneader was evacuated to a vacuum state and stirring was continued, the temperature was raised to 140 ° C, and maintained for 4 hours, and then cooled to room temperature. 35 parts of fumed silica and precipitated silica were weighed according to the formula ratio, and stirring was continued in the kneader for 1 hour to obtain fluorosilicone rubber with in-situ blended silica. The in-situ blended fluorosilicone rubber was added to the internal mixer for stirring, and the internal mixer was kneaded for 5 minutes at room temperature, and the speed was set to 50 rpm. 1.5 parts by mass of heat-resistant agents chromium dioxide and copper oxide were added, and stirred at 50 rpm for 5 minutes at room temperature, followed by adding 2 parts by mass of carbon black dye, and continued to stir at 50 rpm for 5 minutes at room temperature, and then 0.1 parts by mass of solid bis(2-pentyl)sulfurizer and benzamide peroxide were weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 minutes at room temperature. The rubber mix was thinned 8 times in a two-roll open mill, and then hot-pressed in a flat vulcanizer at a temperature of 165°C, a time of 20 min, and a pressure of 20 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 250°C and a time of 2 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0033] The highly wear-resistant rubber materials obtained in Examples 1 to 3 were tested for mechanical properties according to the test method specified in GB / T 528-2009, and for low-temperature brittleness temperature according to the test method specified in GB / T 1682-2014. The oil resistance was tested for the compressive stress relaxation coefficient of the fluorosilicone rubber material after swelling in 15# aviation oil for 72 h at a temperature of 70°C. Tensile strength (MPa) Elongation at break (%) Low temperature brittle temperature (℃) Compression stress relaxation coefficient Example 1 10.8 822.3 -60 0.73 Example 2 9.8 564.0 -60 0.68 Example 3 11.1 416.1 -60 0.73
[0034] The stress-strain curves of Example 1, Example 2 and Example 3 are as follows: Figure 1 As shown, 1# represents the stress-strain curve of fluorosilicone rubber with fumed silica added in an amount of 20 parts and a curing agent of liquid bis(25), 2# represents the stress-strain curve of fluorosilicone rubber with fumed silica added in an amount of 27 parts and a curing agent of liquid bis(25), and 3# represents the stress-strain curve of fluorosilicone rubber with fumed silica added in an amount of 31 parts and a curing agent of liquid bis(25). Figure 1 It can be seen that the fluorosilicone rubber prepared by this method has excellent mechanical properties.
[0035] The scanning electron microscope image of Example 3 is as follows Figure 2 ,Depend on Figure 2 It can be seen that the fumed silica is dispersed relatively evenly in the rubber matrix.
[0036] The transmission electron microscope image of Example 3 is as follows Figure 3 ,Depend on Figure 3 It can be seen that the agglomerates of fumed silica particles are dispersed in fluorosilicone rubber under certain interactions to form a filler network structure.
[0037] Rubber products are used in various systems on aircraft. Their quality is directly related to the operation of the electrical, gas, oil and mechanical transmission systems on the aircraft, and is crucial to the safety, reliability and combat capability of the aircraft. Among them, rubber sealing materials are used in various parts of the aircraft, playing the role of sealing, shock absorption, heat insulation, fire prevention, transmission, support, etc., and are key materials necessary for the realization and guarantee of the functions of various aircraft systems. At the same time, some sealing rubbers come into dynamic contact with other structural parts during use, resulting in friction loss and failure. Therefore, improving the wear and oil resistance of sealing rubber is extremely important for extending the service life and service reliability of sealing parts.
[0038] The rubber materials used in aircraft seals mainly include nitrile rubber, hydrogenated nitrile rubber, fluorine rubber, fluoroether rubber, silicone rubber, polysulfide rubber, polyurethane and EPDM rubber. Currently, nitrile rubber, which is widely used, is very easy to crack in the oil and gas environment, seriously affecting the service life and reliability of the aircraft. Many types of engines have serious consequences such as oil leakage due to the large changes in the cross-sectional dimensions of the nitrile rubber ring after oil resistance, and even cracking. Therefore, it is urgent to develop high-performance rubber sealing materials.
[0039] Fluorosilicone rubber is a type of polymer with a silicon-oxygen bond as the main chain and a fluorine-containing organic group replacing the side chain. It has the dual characteristics of organic silicon materials and organic fluorine materials. The introduction of fluorine atoms makes fluorosilicone rubber have excellent chemical stability, hydrophobicity, oil resistance and solvent resistance, etc. At the same time, it also has the excellent heat resistance, cold resistance, dielectricity, ozone resistance and aging resistance of silicone rubber. These excellent properties of fluorosilicone rubber make it widely used in aerospace, automotive industry and electronic products. At the same time, fluorosilicone rubber can usually be used in fuel media at a temperature of -68 to 230 ℃, but its mechanical properties are relatively poor like ordinary silicone rubber, the surface energy is relatively low, and the processing technology is relatively complicated. Therefore, studying reasonable formulas and processing technology to improve the performance of rubber is the most critical breakthrough point in the application of fluorosilicone rubber.
[0040] Finally, it should be noted that the above embodiments are only used to illustrate rather than limit the technical solutions of the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. Any modification or partial replacement that does not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A high-performance sealing rubber material, characterized in that: The invention comprises the following components in parts by weight: 100 parts of fluorosilicone rubber, 0.1 to 0.8 parts of vulcanizing agent, 10 to 35 parts of reinforcing filler, 1 to 2 parts of heat-resistant agent and 0.5 to 2 parts of black dye.
2. A high performance sealing rubber material according to claim 1, characterized in that: The molecular weight of the fluorosilicone rubber is ≥8*10 5 .
3. The high performance sealing rubber material according to claim 1, characterized in that: The vulcanizing agent is a mixture of one or more of liquid dipentadienyl, solid dipentadienyl, dicumyl peroxide, benzamide peroxide, di-tert-butyl peroxide, and tert-butyl perbenzoate.
4. The high-performance sealing rubber material according to claim 1, characterized in that: The reinforcing filler is a mixture of one or more of fumed silica and precipitated silica.
5. The high-performance sealing rubber material according to claim 1, characterized in that: The heat-resistant agent is a mixture of one or more of titanium dioxide, tin dioxide, iron oxide, copper oxide, nickel oxide, cobalt oxide, and chromium oxide.
6. The high-performance sealing rubber material according to claim 1, characterized in that: The black dye is carbon black.
7. A method for preparing a high-performance sealing rubber material, characterized in that: 100 parts of fluorosilicone rubber are added to a kneader, the kneader is evacuated to a vacuum state and stirring is continued, the temperature is raised to 140 °C, and maintained for 4 hours, and then the temperature is lowered to room temperature; a reinforcing filler is added to the kneader, and stirring is continued in the kneader for 1 hour to obtain an in-situ blended fluorosilicone rubber; the in-situ blended fluorosilicone rubber is added to an internal mixer for stirring, and the internal mixing is performed at room temperature for 5 minutes, and the speed is set to 50 rpm; a heat-resistant agent is added to the internal mixer for mixing and stirring, and the internal mixing is performed at room temperature for 5 minutes, and the speed is set to 50 rpm; a dye is added to the internal mixer for mixing and stirring, and the internal mixing is performed at room temperature for 5 minutes, and the speed is set to 50 rpm; a vulcanizing agent is added to the internal mixer for mixing and stirring, and the internal mixing is performed at room temperature for 10 minutes, and the speed is set to 50 rpm to obtain the mixed fluorosilicone rubber; the mixed fluorosilicone rubber is thinly passed through a double-roll open mill to obtain the desired mixed rubber, and the mixed rubber can be subjected to hot pressing and two-stage vulcanization to obtain a high-performance sealing rubber material.
8. The method for preparing a high-performance sealing rubber material according to claim 7, characterized in that: The rubber mix is thinned in the double-roll mill 8 to 12 times.
9. The method for preparing a high-performance sealing rubber material according to claim 7, characterized in that: The hot pressing temperature of the rubber compound is 160-170°C, the pressure is 10-20 MPa, and the time is 10-20 min.
10. The method for preparing a high-performance sealing rubber material according to claim 7, characterized in that: The second-stage vulcanization temperature of the vulcanized rubber is 200-250°C, and the second-stage vulcanization time is 2-4 hours.
